2006
DOI: 10.1007/s00280-006-0280-z
|View full text |Cite
|
Sign up to set email alerts
|

Androgen and c-Kit receptors in desmoplastic small round cell tumors resistant to chemotherapy: novel targets for therapy

Abstract: DSRCT has significant IHC expression of AR and c-Kit in heavily pre-treated patients. The presence of significant AR expression in 37% suggests that these patients could possibly respond to CAB. The significance of c-Kit expression in 35% of DSRCT patients is unknown and warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 33 publications
0
36
0
3
Order By: Relevance
“…Some of these tumors express androgen receptors and produce CA-125 [181,182]. Approximately a third of DSRCTs express c-Kit [181]. According to a recent Mayo Clinic review, this disease is uniformly fatal [183].…”
Section: Molecular Pathology and Geneticsmentioning
confidence: 97%
See 1 more Smart Citation
“…Some of these tumors express androgen receptors and produce CA-125 [181,182]. Approximately a third of DSRCTs express c-Kit [181]. According to a recent Mayo Clinic review, this disease is uniformly fatal [183].…”
Section: Molecular Pathology and Geneticsmentioning
confidence: 97%
“…The desmoplastic appearance of these tumors is consequential to the constitutive activation of platelet-derived growth factor (PDGF)-α and FGFR4 [178][179][180]. Some of these tumors express androgen receptors and produce CA-125 [181,182]. Approximately a third of DSRCTs express c-Kit [181].…”
Section: Molecular Pathology and Geneticsmentioning
confidence: 99%
“…Another attempt at developing treatments for this disease was the use of a novel molecularly targeted therapy and a new chemical agent (15). We examined the expression of c-kit, androgen receptor, CD20 and epidermal growth factor receptor using a biopsy sample (16,17). However, we found that none of the markers were expressed in tumor cells; therefore, we could not use any molecularly targeted agent in this case.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for male preponderance is unknown. In one study androgen receptors were present in 10/27 (37%; P = 0.0045) [10].…”
Section: Introductionmentioning
confidence: 96%
“…The general pattern of treatment failure is recurrent disease first in the peritoneal cavity, then in the liver, and finally in distant sites. Patients typically are young (ages 5-30 years) at presentation and 80-90% are males [3,[8][9][10][11]. The reason for male preponderance is unknown.…”
Section: Introductionmentioning
confidence: 99%